Implementing Palliative and End-of-Life Care in Lung Cancer: When to Start? - Haryati Haryati; Desi Rahmawaty; Tenri Ashari Wanahari (Faculty of Medicine Universitas Airlangga, 2023)
Lung cancer is among the most prevalent cancers and the primary cause of cancer-related mortality. Despite advances in treatment, patients often have a poor prognosis, with a limited survival period, particularly in advanced stages. Significant morbidity is linked with lung cancer, and symptoms are frequently inadequately controlled, resulting in a considerable symptom burden for patients and their family caregivers. It is typically accompanied by an overall reduction in one's quality of life (QoL). Palliative care is an established therapy paradigm that successfully enhances symptom management and physical and mental health. It can be initiated as soon as the patient develops symptoms (even in the early stage) or is diagnosed with a late stage. Over the past few decades, palliative care has become a vital part of comprehensive care for people, especially those with advanced diseases. Early palliative care (EPC) integration within the oncology setting is more effective than standard care in enhancing the patient's QoL and length of survival, resulting in less intrusive end-of-life care. When caring for lung cancer patients, medical practitioners must remember their duty to cure occasionally, routinely alleviate, and constantly comfort the patient. Treating physical symptoms, illness comprehension, coping, and psychological and spiritual anguish are all vital components. Intervention strategies by multidisciplinary teams concentrating on the patient and their family and dealing with the circumstances are essential. All health providers should prioritize palliative and end-of-life care to enhance care and assist patients and their families in navigating the final period of life.